2016
DOI: 10.32677/ijch.2016.v03.i01.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of current status of lead toxicity among children: A hospital based cross-sectional study

Abstract: Introduction: Lead is a highly toxic non-essential metal. Children have a wide spectrum of subclinical and clinical effects due to lead exposure and lead poisoning. Objectives: To identify the extent of the problem of lead toxicity among children and its association with anthropometry, nutritional status and awareness about lead toxicity. Materials and Methods: Study population comprised children admitted in CSI Hospital as inpatients. Purposive sampling was done to enroll patients with no risk of lead exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…Comparable results have been obtained in previous studies of primary school children of Birgunj Municipality [ 17 ] and Kathmandu Municipality [ 18 ], highlighting a continuous health risk in this setting. Such higher elevated blood levels (BLLs ≥5 μg/dl) among children have also been reported in studies conducted in India [ 19 , 20 ]. Similarly, studies conducted in China have also shown a prevalence of elevated BLLs among children, including more than 54% in Jintan [ 8 ] and 44% in Wuhan[ 21 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Comparable results have been obtained in previous studies of primary school children of Birgunj Municipality [ 17 ] and Kathmandu Municipality [ 18 ], highlighting a continuous health risk in this setting. Such higher elevated blood levels (BLLs ≥5 μg/dl) among children have also been reported in studies conducted in India [ 19 , 20 ]. Similarly, studies conducted in China have also shown a prevalence of elevated BLLs among children, including more than 54% in Jintan [ 8 ] and 44% in Wuhan[ 21 ].…”
Section: Discussionsupporting
confidence: 64%
“…In our study, BLLs were higher among boys. Higher BLL among boys was also reported in other studies from Nepal [ 17 , 18 ], India [ 19 , 20 ] and China [ 8 , 21 , 22 ] Although elevated BLLs have been found to be positively correlated with the age of children [ 8 , 19 , 20 , 22 , 23 ] we did not find such association in our study.…”
Section: Discussionsupporting
confidence: 61%